Rhizosphere impacts bacterial community structure in the tea (Camellia sinensis (L.) O. Kuntze.) estates of Darjeeling, India. (4th January 2022) - Bhattacharyya, Chandrima; Imchen, Madangchanok; Mukherjee, Triparna; Haldar, Shyamalina; Mondal, Sangita; Mukherji, Shayantan; Haldar, Anwesha; Kumavath, Ranjith; Ghosh, Abhrajyoti
Summary: India contributes 28% of the world's tea production, and the Darjeeling tea of India is a world‐famous tea variety known for its unique quality, flavour and aroma. This study analyzed the spatial distribution of bacterial communities in the tea rhizosphere of six different tea estates at different altitudes. The organic carbon, total nitrogen and available phosphate were higher in the rhizosphere soils than the bulk soils, irrespective of the sites. Alpha and beta diversities were significantly ( p < 0.05) higher in the bulk soil than in the rhizosphere. Among the identified phyla, the predominant ones were Proteobacteria, Actinobacteria and Acidobacteria. At the genus level, only four out of 23 predominant genera (>1% relative abundance) could be classified, viz., Candidatus Solibacter (5.36 ± 0.36%), Rhodoplanes (4.87 ± 0.3%), Candidatus Koribacter (2.3 ± 0.67%), Prevotella (1.49 ± 0.26%). The rhizosphere effect was prominent from the significant depletion of more ASVs ( n = 39) compared to enrichment ( n = 11). The functional genes also exhibit a similar trend with the enrichment of N2 fixation genes, disease suppression and Acetoin synthesis. Our study reports that the rhizobiome of tea is highly selective by reducing the alpha and beta diversity while enriching the significant functional genes.